2006
DOI: 10.1111/j.1574-6968.2006.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

EspC, an autotransporter protein secreted by enteropathogenic Escherichia coli (EPEC), displays protease activity on human hemoglobin

Abstract: Some enteropathogenic Escherichia coli (EPEC) strains, which are an important cause of diarrhea among infants, secrete a serine protease autotransporter protein called EspC. The pathogenic role of EspC upon EPEC infection is unknown. In this study, we demonstrated that purified EspC protein, obtained from supernatants of EPEC cultures, interacted with hemoglobin and degraded it. Moreover, we have shown that EspC is a hemin-binding protein. We hypothesized that hemoglobin proteolysis by EspC may contribute to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Upon delivery to the exterior of the cell via the T5SS, EspC interacts with EspA and is internalized during pedestal formation via the T3SS translocon (138,139). EspC confers enhanced lysozyme resistance to EPEC (140), and purified EspC has been shown to interact with and degrade hemoglobin (141) and to hydrolyze other proteins such as pepsin, factor V, and spectrin (142). Additionally, oligomerization of EspC gives rise to rope-like structures that serve as a substratum for adherence and biofilm formation as well as to protect bacteria from antimicrobial compounds (143).…”
Section: Pathogenesismentioning
confidence: 99%
“…Upon delivery to the exterior of the cell via the T5SS, EspC interacts with EspA and is internalized during pedestal formation via the T3SS translocon (138,139). EspC confers enhanced lysozyme resistance to EPEC (140), and purified EspC has been shown to interact with and degrade hemoglobin (141) and to hydrolyze other proteins such as pepsin, factor V, and spectrin (142). Additionally, oligomerization of EspC gives rise to rope-like structures that serve as a substratum for adherence and biofilm formation as well as to protect bacteria from antimicrobial compounds (143).…”
Section: Pathogenesismentioning
confidence: 99%
“…Once there, the C terminus of the protein generates a ␤-barrel in the outer membrane that allows the passenger domain to exit the cell (68). Hemoglobin proteases from E. coli belong to the SPATE (serine protease autotransporter proteins of Enterobacteriaceae) family of proteins and are only found in pathogenic strains (68,69). E. coli hemoglobin proteases are thought to bind the released heme and deliver it to an unknown surface receptor (68).…”
Section: Bacterial Iron and Heme Acquisition Systemsmentioning
confidence: 99%
“…Recently, it was also found that EspC conferred enhanced lysozyme resistance to EPEC (16). EspC and EspP display enzymatic activities, and although EspC cleaves spectrin (also called fodrin) and hemoglobin, EspP of EHEC cleaves pepsin A, and human coagulation factor V (2,11,14,(17)(18)(19). The EspP protein was also shown to influence gut colonization in calves and contributes to adherence of EHEC to bovine primary rectal cells (20).…”
mentioning
confidence: 99%